2005
DOI: 10.1097/01.psy.0000155664.13300.64
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Hypersensitivity: A Systematic Review of Provocation Studies

Abstract: The symptoms described by "electromagnetic hypersensitivity" sufferers can be severe and are sometimes disabling. However, it has proved difficult to show under blind conditions that exposure to EMF can trigger these symptoms. This suggests that "electromagnetic hypersensitivity" is unrelated to the presence of EMF, although more research into this phenomenon is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
1
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 20 publications
6
131
1
10
Order By: Relevance
“…4 Investigasi yang lebih baru telah berfokus terutama efek langsung paparan medan listrik terhadap jantung, terutama yang berkaitan dengan variabilitas detak jantung dan pengaruhnya pada kejadian kardiovaskular akut lainnya. 5 Selain itu, penelitian oleh Mohamed dkk. 6 mengenai efek paparan medan listrik yang dilakukan terhadap tikus menunjukkan peningkatan tekanan darah sistol serta ditemukan hipertrofi, fragmentasi, dan vakuolasi miokardium tikus yang mendapat paparan selama 3 (tiga) jam/hari dalam waktu empat minggu.…”
Section: Pendahuluanunclassified
“…4 Investigasi yang lebih baru telah berfokus terutama efek langsung paparan medan listrik terhadap jantung, terutama yang berkaitan dengan variabilitas detak jantung dan pengaruhnya pada kejadian kardiovaskular akut lainnya. 5 Selain itu, penelitian oleh Mohamed dkk. 6 mengenai efek paparan medan listrik yang dilakukan terhadap tikus menunjukkan peningkatan tekanan darah sistol serta ditemukan hipertrofi, fragmentasi, dan vakuolasi miokardium tikus yang mendapat paparan selama 3 (tiga) jam/hari dalam waktu empat minggu.…”
Section: Pendahuluanunclassified
“…Typical subjective sensations and symptoms are described as headache, dizziness, fatigue, and nausea. Evidence to support these hypotheses has been sparse and never successfully replicated (2,3).…”
Section: Editorialmentioning
confidence: 99%
“…There seems to be geographical variation in both the type of symptoms reported and the attributed source association (Irvine, 2005). However, EHS individuals have not been able to recognize exposed from sham conditions under controlled experiment conditions (Rubin et al, 2005;Roosli, 2008), and thus appear not to fulfill the fundamental criteria for proof of causality (Ward, 2009). In contrast, experimental data showed that people from the general population are able to detect 50 Hz electric currents well below an established perception threshold limit of 500 mA (IEC, 1994), with on average women being more susceptible than men (Leitgeb and Schroettner, 2002).…”
Section: Introductionmentioning
confidence: 99%